THE RELATIONSHIP BETWEEN THE LEVEL OF HIGHLAND HORTICULTURAL FARMERS' COMPLIANCE IN PESTICIDE APPLICATION AND THE PRESENCE OF PESTS AND DISEASES - Yunanda Audri Balqis Yunanda; Suparman SHK; Chandra Irsan (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2023)
Currently, many farmers are still very unfamiliar with using pesticides correctly and appropriately which lead environment pollution, population reduction of natural enemies and people health. The aims of this research were to determine the impact or influence of farmers obedience in applicating pesticide on the incidence of pests and diseases on highland horticultural cultivation, the presence of natural enemies, and level of pesticide residues in their horticultural products. This research was conducted in highland horticultural cultivation areas in Pagar Alam, South Sumatra. Data on farmers obedience in applicating pesticide was collected by interviewing eligible farmers by using questionnaires. Data on pests and disease incidence was collected by direct observation on the interviewed farmer's horticultural field. The variable measured were pest population and the in-tensity of damage of each pest, incidence and intensity of each disease and natural enemy type and population. The relationship between the level of farmer obedience in applicating pesticide and incidence of pests and dis-ease on their respected lands was determined by calculating their correlation coefficient. The results showed that there were significant correlations between the level of farmers obedience in applicating pesticide and the incidence as well as intensity of pests and diseases of highland horticultural crops.